2017
DOI: 10.4067/s0718-34292017005000002
|View full text |Cite
|
Sign up to set email alerts
|

Evaluación de portainjertos criollos de Lagenaria siceraria en la producción de sandía injertada

Abstract: El injerto en hortalizas es una alternativa en los sistemas de producción de cultivos bajo condiciones adversas, siendo de mayor importancia portainjertos de Cucurbita y Lagenaria en el cultivo de sandía. La especie Lagenaria siceraria se encuentra distribuida en México; sin embargo, el uso de materiales criollos como portainjerto es limitado o nulo, por lo que, la presente investigación tuvo como objetivo evaluar y seleccionar las mejores combinaciones de portainjertos criollos de L. siceraria en dos variedad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 11 publications
(12 reference statements)
0
6
0
1
Order By: Relevance
“…The need for drought-resistant crops is critical and will surely grow in the coming years, considering the notable degradation of soil and water resources, and the accelerating effects of global climate change. In this context, the L. siceraria breeding programs for rootstock should therefore incorporate key root phenotypes (including morphological and anatomical traits) that focus on water capture and nutrient uptake, and which are suited for sustainable production in cucurbit crops (Suárez-Hernández et al, 2017 , 2022 ), as well as those of watermelon, melon and cucumber (Suárez-Hernández et al, 2017 , 2022 ). On the other hand, the traits that affect the metabolic efficiency of root growth and soil exploration should therefore also be important components of drought tolerance and plant productivity, the effects of which should be evaluated in different combinations of rootstock varieties.…”
Section: Discussionmentioning
confidence: 99%
“…The need for drought-resistant crops is critical and will surely grow in the coming years, considering the notable degradation of soil and water resources, and the accelerating effects of global climate change. In this context, the L. siceraria breeding programs for rootstock should therefore incorporate key root phenotypes (including morphological and anatomical traits) that focus on water capture and nutrient uptake, and which are suited for sustainable production in cucurbit crops (Suárez-Hernández et al, 2017 , 2022 ), as well as those of watermelon, melon and cucumber (Suárez-Hernández et al, 2017 , 2022 ). On the other hand, the traits that affect the metabolic efficiency of root growth and soil exploration should therefore also be important components of drought tolerance and plant productivity, the effects of which should be evaluated in different combinations of rootstock varieties.…”
Section: Discussionmentioning
confidence: 99%
“…Candir et al [53] recorded values of 10.1 • Brix to 12.6 • Brix when grafting Crimson Tide variety on 21 accessions of L. siceraria, identifying five statistically greater accessions. Suárez-Hernández et al [13] confirm differential L. siceraria rootstocks responses, reporting that five out of six accessions of L. siceraria presented significantly higher content of soluble solids in Sangria variety, while these same rootstocks in the 2800 variety presented similar values compared to ungrafted fruit. This indicates that the response depends on the interaction between rootstock and variety to be grafted.…”
Section: Fruit Internal Characteristicsmentioning
confidence: 83%
“…Studies conducted by Yamasaki et al [34] and Yetisir et al [48] also agree on pointing out that L. siceraria rootstocks do not modify pulp firmness. On the contrary, Suárez-Hernández et al [13] reported a reduction between 14.5% and 33.0% in firmness of watermelon cv. 2800 and Sangria when grafted on four accessions of L. siceraria.…”
Section: Fruit Internal Characteristicsmentioning
confidence: 90%
See 1 more Smart Citation
“…Si bien en nuestro caso se observó un ligero aumento en la firmeza de la fruta en plantas injertadas (Tabla 1), estas diferencias no fueron significativas, puesto que la firmeza depende más del momento del corte y las condiciones ambientales (Orrala-Borbor et al, 2018). Asimismo, se debe tener en cuenta que la firmeza de la pulpa es un atributo relacionado con varios factores morfológicos (Suárez-Hernández et al, 2017). La clasificación del fruto de sandía en el mercado mayorista de Lima se hace por el peso.…”
Section: Resultados Y Discusiónunclassified